Global biodiversity conservation measures - Khan, T I; Ai-Ajmi, Dhari N (Jaipur Pointer, 1999)
The book contains chapters contributed by scientists working in England, U.K. Kuwait, India, United State of America, Saudi Arabia,Philippines,etc. Pertaining to measures taken for biodiversity conservation. Biodiversity is the variability, among living o
Keywords: Biological diversity; Biological diversity conservation; Plant diversity conservation